История лексем дознаться и заслышать в русском и других восточнославянских языках - Павловна Гарбуль, Людмила (Slavistica Vilnensis, 2010)
The article examines the history of the following words found in diplomatic correspondence of Muscovite Russia of the first half of the 17th century: doznatisia ‘find out; ascertain’ and zaslyšati ‘hear about, of; learn, get to know; ascertain; clear up’. The author aims at proving that these intraslavonic derivates are interslavonic lexical loan-words-Polonisms in the Russian written language of the 17th century and in the other East Slavonic languages of the 16th century, and also at retracing their further history in these languages.The following conclusions are made: both examined words in the analysed meanings, in the opinion of the author, are lexical loan-words-Polonisms in the Russian language of the 17th century and in the written language of the Great Duchy of Lithuania of the 16th century. The “prostaja mova”, evidently, became the mediator for the words doznatisia and zaslyšati to be borrowed by the Russian written language. The materials of the article specify the chronology of both words in the Russian written language. The words doznat’sia and zaslyšat’ in the analysed meaning are in usage in the contemporary spoken Russian. The first of these words is also in active usage in the contemporary literary Byelorussian and Ukrainian languages.